A study on the relationships between production, export, stock level and soybean oil price towards price fluctuations of Malaysian Crude Palm Oil / Wan Mohd Hazimin Wan Mohd Fauzi - Wan Mohd Fauzi, Wan Mohd Hazimin (2005)
This project paper consists of five chapters. The first chapter is general introduction of the study, second chapter is discussing the literature review, third chapter is the research methodology, the fourth chapter is about the finding and data analysis and lastly is chapter five that discussing about the conclusions and recommendations. This project paper is concerned about the study on the relationship between production quantity. export quantity, stock level and soybean oil price towards price fluctuations of Malaysian crude palm oil prices. The objective of this study is to determine whether the production quantity, export quantity, stock level and soybean oil price have contributed towards price fluctuations of Malaysian crude palm oil prices. All the data used in this study is monthly data and the duration is nine years from 1995 to 2003. The data is tested through the SPSS software and the result of this study shows that the production quantity, export quantity, stock level have negative relationship towards price fluctuations of Malaysian crude palm oil and only soybean oil price has positive relationship towards price fluctuations of Malaysian crude palm oil.